Antibacterial Effects of Bioactive Boswellic Acids Loaded Chitosan Nanoparticles against Gram-Positive and Gram-Negative Bacteria - Rathi, Neeta; Kumar, Satyender; Seema; Dureja, Harish (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Boswellic acids are naturally occurring pentacyclic terpenoids that have revealed valuable anti-inflammatory, antiproliferation and anticancerous activities. Instead of these effects boswellic acids also possess antibacterial potential reported in the literature. However, these phytoconstituents associated with low aqueous solubility and bioavailability restrictions. The present study aimed to explore the antibacterial effects of boswellic acids by means of nano formulations. Materials and Methods: Chitosan was utilized as a natural biocompatible material for nanoparticles preparation, employing the ionic gelation technique as an effective approach. Well diffusion method was used to test antibacterial activity against four pathogenic bacteria (Gram-positive bacteria: Staphylococcus aureus, Bacillus subtilis; Gram-negative Salmonella typhi, and. Escherichia coli. Micro broth dilution technique was used to determine the minimum inhibitory concentration. Results: Boswellic acids-loaded nanoparticles displayed spherical particles with particle size 104.6 nm and 0.081 PDI value, respectively with smooth-surfaced spherical particles. Boswellic acids chitosan nanoparticles have a greater zone of inhibition against Salmonella typhi than Boswellia serrata extract with MIC values of 3.91 and 7.81 μg/ mL, respectively. Conclusion: Poorly soluble boswellic acids were successfully encapsulated in chitosan nanoparticles and exhibited improved antibacterial activity compared to Boswellia serrata extract.
Keywords: Boswellic acids; Chitosan nanoparticles; Antibacterial activity